ANALISIS PENERAPAN METODE LINE OF BALANCE (LOB) PADA PROYEK PEMBANGUNAN RUANG KELAS BARU MADRASAH IBTIDAIYAH NEGERI 5 MALUKU TENGAH - Lessy, Gheisberth Tontji; Jamlaay, Octovianus; Saleh, La Mohamat (Journal Agregate, 2024)
Construction projects that have repetitive or repetitive work packages such as housing, school buildings, apartments, hotels, highways or manufacturing industry projects require a project scheduling method that is able to accommodate continuous and well scheduled resource requirements without the occurrence of a hitch. In the New Classroom Development Project for Madrasah Ibtidaiyah Negeri 5 Central Maluku, the author reviewed using the S – Curve scheduling method and experienced delays in implementation due to rainy weather, delays in material mobilization and lack of manpower, so the author will analyze scheduling with a special method for repetitive work, namely by using the methodLine of Balance (LoB). Method Line of Balance (LoB) is a project scheduling method that can provide productivity levels and duration information in graphical format and can show activity progress, and can detect potential disturbances or conflicts in work items to be worked on. This research stage is obtained from the datatime schedule a plan that aims to redraw to detect conflicts in work items. From the results of the research, the use of the methodLine of Balance (LoB) simplification of repetitive work activities for structural work and architectural work from the first floor to the second floor makes it easier to analyze which is then depicted in a line chart and the results of the analysis show the methodLine of Balance(LoB) can detect conflicts or lines of work activity that intersect, among others, Structural Work of the second floor intersects with Wall and Plastering of the first floor, Wall and Plastering of the second floor intersects with Ceiling Works of the second floor, Sanitair Works of the first floor intersects with Aluminum Works Composite Panel (ACP) on the first floor and from the calculation results obtained the final scheduling duration of 84 days or 12 weeks and from the results of the analysis showed that the LoB method was effective in its use in the New Classroom Development project at Madrasah Ibtidaiyah Negeri 5 Central Maluku because it was able to detect disturbances in the Curve – S of LoB chart depiction